THE EFFECT OF TEACHER INVOLVEMENT AND PARENT PARTICIPATION ON STUDENT LEARNING ANXIETY WITH ACADEMIC MOTIVATION AS AN INTERVENING VARIABLE IN SENIOR HIGH SCHOOL ECONOMICS COURSES IN PINRANG REGENCY - Nur Rezky Asman; Basri Bado; Tuti Supatminingsih (SOSIOEDUKASI, 2025)
This study aims to analyze the effect of teacher involvement and parent participation on student learning anxiety with academic motivation as an intervening variable in economics subjects at senior high schools in Pinrang Regency. This study is quantitative in nature, with data collected through questionnaires administered to students from three schools with A, B, and C accreditation levels. The data were analyzed using the SmartPLS software. The results show that teacher involvement and parental participation have a positive and significant effect on students' academic motivation and a negative effect on learning anxiety. In addition, academic motivation is proven to be a variable that mediates the relationship between teacher involvement and parental participation on learning anxiety. This means that the higher the teacher involvement and parental support, the higher the students' academic motivation and the lower their level of learning anxiety. These findings emphasize the importance of collaboration between teachers, parents, and schools in creating a positive learning environment to support students' emotional well-being and academic achievement.